BS EN 50377-15-1. Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Part 15-1. Type MPO with 12 fibre PPS ferrules terminated on EN 60793-2 category A1a multimode fibre for 50/125 micron multimode fibre. macrobend enhanced fibre only (25th March 2020) - British Standards Institution,
No abstract available